Truthful incentive mechanism for “digital currency”based on privacy protection - Xiao CHEN; Xinran LYU; Zhi LIU (网络与信息安全学报)
Many national central banks have conducted legal digital currency research based on distributed ledger technology,but only the UK has disclosed the accounting structure of the legal digital currency framework RSCoin,and the incentive mechanisms was proposed to encourage mintettes to provide honest collaborative accounting services.However,this mechanism does not take into account the differential service costs of mintettes,nor does it give a definite compensation distribution.The privacy costs of the mintettes were fully considered,the incentive model of the central bank and mintettes were established,and the methods were clarified to compensate mintettes.In the legal digital currency research area,an incentive mechanism POPTIM was proposed firstly,that not only protects the private cost of the mintettes,but also guarantees the mintettes report their truthful bidding prices to the central banks.POPTIM first encrypts the biddings of mintettes by coding hash encryption method,then adopts privacy-preserving sorting algorithm to select the winner mintettes,and finally calculates the reward of mintettes based on the homomorphic addition algorithm.The analysis shows that the mechanism is privacy security,computationally efficient,individually rational and truthful simultaneously.